Streptococcal toxic shock syndrome following total thyroidectomy - Forsythe, J (Ann R Coll Surg Engl, 2014)
Hung JA, Rajeev P. Streptococcal toxic shock syndrome following total thyroidectomy. Ann R Coll Surg Engl 2013; 95: 457–460 doi 10.1308/003588413X13629960048118